New Approaches to Urban Refugee Livelihoods - Buscher, Dale (Refuge: Canada's Journal on Refugees, 2013)
Increasingly refugees live in urban areas—usually in slums impacted by unemployment, poverty, overcrowding and inadequate infrastructure. Host governments often restrict refugees’ access to the labor market, access that can be further impeded by language barriers, arbitrary fees, and discrimination. UNHCR and its partners are seldom equipped to understand and navigate the complex urban economic environment in order to create opportunities for refugees in these settings. Based on assessments undertaken in 2010 and 2011 in Kampala, New Delhi and Johannesburg, research findings indicate that refugees in urban areas adopt a variety of economic coping strategies, many of which place them at risk, and that new approaches and different partnerships are needed for the design and implementation of economic programs. This paper presents findings from the assessments and lays out strategies to address the challenges confronting urban refugees’ ability to enter and compete in the labor market.